Asthma Knowledge and Asthma Management Behavior in Urban Elementary School Teachers - Unikel, Lynne H. (J Asthma, 2010)
BACKGROUND: While schools are an important setting for asthma care in youth, teachers’ asthma knowledge and symptom management is poor. This study investigated the knowledge, prevention and management behaviors, and communication regarding asthma of teachers of low income ethnic minority students. It was hypothesized that relative to colleagues whose students did not have active asthma (i.e., did not have symptoms during the day), teachers of students with active asthma would have better asthma knowledge and that more would take asthma prevention steps and communicate with parents and school nurses. METHODS: Drawing from 25 elementary schools in NYC, 320 Pre-Kindergarten through 5(th) grade classroom teachers with at least one student with asthma completed measures assessing their asthma knowledge, steps taken to manage asthma, communication with the school nurse or parents, information they received about asthma and whether or not they had at least one student in their class experience asthma symptoms. T-test and chi-square were used to test hypotheses. RESULTS: Asthma knowledge varied among teachers. Most could identify potential triggers, yet few knew that medication taken prior to exercise could prevent symptoms and that students with asthma need not avoid exercise. Communication between teachers and school nurses and between teachers and parents was lacking. Relative to colleagues whose students did not have active asthma, teachers whose students had active asthma had better asthma knowledge; more took steps to prevent students from having asthma symptoms, communicated with parents and initiated communication with the nurse. CONCLUSIONS: Teacher knowledge about asthma and asthma management is limited, especially among those whose students did not have active asthma. Teachers respond reactively to students who have symptoms in class by increasing prevention steps and communications with parents and the school nurse. A more proactive approach to managing asthma in schools is warranted.